Advanced ESL Students' Prior EFL Education and Their Perceptions of Oral Corrective Feedback - Lee, Eun Jeong Esther (Journal of International Students, 2018)
The author in this study examines how advanced-level adult English as a Second Language (ESL) students’ previous English as a Foreign Language (EFL) classroom experiences influence their perceptions of their teachers’ oral corrective feedback (CF). It uses in-depth qualitative data to characterize the participants’ prior English learning, and to determine how their experiences influence how they perceive CF in ESL classrooms. Understanding these patterns of perception will enhance ESL professionals’ abilities to create effective and culturally sensitive ESL classrooms.